Legal scholarship for the urban core : from the ground up / edited by Peter Enrich, Rashmi Dyal-Chand. - Enrich, Peter D.; Dyal-Chand, Rashmi, 1970- (Cambridge University Press, 2019)
The problems of entrenched poverty and economic underdevelopment in American urban cores involve multiple overlapping challenges that have stymied consistent and long-term progress for many decades. Although inadequate and misguided laws are not solely responsible for this state of affairs, good laws - and good lawyering - can contribute enormously to overcoming the challenges of the urban cores. By showcasing a range of scholarly analyses, covering a broad spectrum of legal issues and methodologies, this book demonstrates how law and lawyers can and do respond to the challenges of the urban cores. It provides paths forward at the local level in the face of federal political paralysis and inattention and lays a foundation for new paradigms and new approaches to intransigent problems. Modeling engaged legal scholarship as a pragmatic response to contemporary challenges, this book is for anyone concerned about the current state of American urban cores.